National Strategies To Promote Renewable Energy Development: Whither Nigeria? - Ajibade, Andrea A. (Journal of Sustainable Development Law and Policy, 2025)
Renewable energy (RE) development enhances electrification, mitigates climate change and aids energy efficiency. Kenya, South Africa and Ghana, among other states within sub-Saharan Africa, have established legal regimes to integrate renewable energy into their energy mix. Through defined legal strategies for RE deployment, these states have committed to the promotion, development and utilization of RE. Despite the momentum towards renewable energy development across the region, Nigeria’s efforts fall short of establishing effective legal strategies. As Africa’s most populous nation it must do more to make RE part of its energy mix in order to impact electrification rates, mitigate climate change and aid socio-economic conditions. This article appraises the legal strategies for RE development in Kenya, South Africa and Ghana. Against this appraisal, it critically evaluates Nigeria’s legal strategies to promote and develop RE. It recommends legal reforms that are necessary to better integrate RE into Nigeria’s energy mix. The methodological approach of this article is doctrinal and library-based. It includes primary and secondary sources. Primary sources include laws, statutes, legal documents, conventions and statistics. Secondary sources include journal articles, internet sources and newspaper articles. All sources are subject to content analysis. It is expected that the article will be useful to policy and lawmakers across various tiers of government in Nigeria.